Блочна каталітична система знешкодження монооксиду вуглецю на основі газобетону - Іваненко, Олена Іванівна; Радовенчик, Вячеслав Михайлович; Карвацький, Антон Янович; Мікульонок, Ігор Олегович; Плашихін, Сергій Володимирович; Оверченко, Тетяна Анатоліївна; Носачова, Юлія Вікторівна; Довголап, Сергій Дмитрович (Вісник НТУУ “КПІ імені Ігоря Сікорського”. Серія: Хімічна інженерія, екологія та ресурсозбереження, 2021)
The paper presents the results of a study of catalysts for the conversion of carbon monoxide based on aerated concrete, modified with magnetite and chromium ferrite separately and in aggregate. It was found that at a consumption of 100 g of catalyst powder per 1 dm3 of a typical mixture for producing aerated concrete and obtaining blocks of modified aerated concrete according to the traditional technology, their efficiency is 70-85% at 400 °C and decreases to 9-13% at 200 °C. In terms of strength and physicochemical properties, aerated concrete samples differ little from standard ones, and in some cases even exceed them. The proposed method for fixing catalyst particles in blocks of aerated concrete makes it possible to build fundamentally new schemes for neutralizing carbon monoxide when placing modified blocks directly at the loading of electrode raw materials in furnaces. This greatly simplifies the conversion process and its control system.